(untitled) (Global Journal of Human-Social Science, 2018)
Recognition of the elements of the interpretive narrations by using scientific methods will open the way to a comprehensive understanding of the words of the Fourteen Infallibles (S.A.). This way in which accessing, analyzing and discussing the most important subjects focused by the Holy Prophet (S) and the other infallibles (A.S.) prepares the ground for starting a discussion and hypothesizing. This research tries to answer the question, what dimensions and components the interpretive narrations of the Sūrat al-Isrᾱ of the Holy Qur’an have and how they are distributed in the phrases. Allocating about half of the narrations to the recognition of the true guides indicates that the necessity of giving insight and awareness with regard to the station of the prophets, especially the Prophet of Islam (S), the Imamate and Ahl al-bayt (A.S.) was focused by the Infallibles.